Chiral Water-Soluble Molecular Capsules With Amphiphilic Interiors - Sakowicz, Arkadiusz Marek; Szumna, Agnieszka (Frontiers in Chemistry, 2022)
We present the synthesis of new chiral water-soluble dimeric capsules by the multicomponent Mannich reaction between charged amino acids (glutamic acid or arginine), resorcinarene, and formaldehyde and subsequent self-assembly. The zwitterionic character of the backbones enables electrostatic interactions between arms and induces self–assembly of dimeric capsules (L-ArgR)2 and (L-GluR)2 in water in a wide range of pH, as demonstrated by NMR, diffusion coefficient measurement, and circular dichroism. The assembly/disassembly processes are fast on the NMR timescale. This mode of dimerization leaves side chains available for additional interactions and creates chiral cavities of mixed hydrophobic/hydrophilic character. According to this characteristic, capsules do not bind fully nonpolar or fully polar guests but effectively encapsulate a variety of chiral molecules with mixed polar/apolar character (aliphatic and aromatic aldehydes, epoxides, alcohols, carboxylic acids, amines, and amino acids) with moderate strength. We also demonstrate formation heterocapsules (GluR)(ArgR) (homo- and heterochiral) that utilize additional interactions between charged acidic and basic side chains and have encapsulation properties better than those of the homodimers.